2020
DOI: 10.20435/multi.v26i62.3046
|View full text |Cite
|
Sign up to set email alerts
|

A tríade sarcopenia, disfagia e desnutrição em pacientes internados para reabilitação em um hospital de retaguarda

Abstract: A tríade sarcopenia, disfagia e desnutrição tem sido estudada devido a sua provável associação. Nos pacientes internados para reabilitação, é possível identificar perdas consideráveis de massa muscular, o que influencia diretamente essas três condições. O estudo objetivou identificar a frequência com que pacientes admitidos para reabilitação, em um hospital de retaguarda, apresentam sarcopenia associada à desnutrição e à disfagia. O trabalho foi do tipo quantitativo, transversal, prospectivo e contou com a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…A study (17) involving hospitalized patients also found similar results, with 38.8% of the participants with potential dysphagia also presenting sarcopenia. Conversely, another study (18) pointed out the simultaneous occurrence of dysphagia and sarcopenia in 69.5% of hospitalized elderly, thus differing from our results.…”
Section: Discussionsupporting
confidence: 52%
“…A study (17) involving hospitalized patients also found similar results, with 38.8% of the participants with potential dysphagia also presenting sarcopenia. Conversely, another study (18) pointed out the simultaneous occurrence of dysphagia and sarcopenia in 69.5% of hospitalized elderly, thus differing from our results.…”
Section: Discussionsupporting
confidence: 52%
“…Um estudo (17) com indivíduos hospitalizados também encontrou resultados semelhantes, 38,8% dos participantes com provável disfagia apresentaram também sarcopenia. Outro estudo (18) demonstrou simultaneamente disfagia e sarcopenia em 69,5% dos idosos hospitalizados, divergindo dos resultados desse estudo.…”
Section: Discussionunclassified